Models for the effect of rising water in abandoned mines on seismic activity. (July 2015) - Fowkes, Neville; Hocking, G.; Mason, D.P.; Please, C.P.; Kgatle, R.; Yilmaz, H.; van der Merwe, N.
Abstract: The old closed gold mines on the Witwatersrand are flooding and there is concern that the water may seep into stable faults in the district and destabilise them, thus leading to greater seismic activity. The simple deterministic models described here suggest that the time span for water movement into such faults within a distance of 3000 m is likely to be of the order of months and that the hydrostatic pressure buildup within the filled cracks is likely to significantly increase the risk of fault slip. These results appear to be consistent with available observations as documented by Goldbach[20] . The simple models predict a linear decrease in the effective coefficient of friction of the water filled fault with water depth with a reduction of up to 30% possible. Furthermore, and importantly, slip is predicted to occur along joints and faults not previously prone to slip because of their unfavored orientation. Abstract : Highlights: We assess the effect of water drainage from abandoned mines on seismic activity. Models suggest that the time scale for water movement into neighbouring faults is months. About a 20% increase in the coefficient of friction is expected due to water entry into faults at 2000 m. Formally inactive faults become active as a result of water entry.